This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This problem can be solved by breaking it up, and first solving the cube root. 3 3 = 2 7 3 √ 2 7 = 3 • 3 • 3 = 2 7 , s o , 3 √ 2 7 = 3 Now that we know the cube root, we must solve everything in the parenthesis and then do the outer math: 1 6 • 3 = 4 8 , a n d , 4 8 2 = ∗ ∗ 2 3 0 4 ∗ ∗
Are you asking for the value of ( 1 6 3 3 3 ) 2 ?
It was hard to read what you typed up.
Yes. very sorry.
Log in to reply
Thanks. I have edited the problem for clarity.
As the problem creator, you can click on "Edit problem" in the menu to see how I typed in the LaTeX. Alternatively, you can click on "Toggle Latex" in the menu to have the equations displayed in LaTeX form.
Problem Loading...
Note Loading...
Set Loading...
( ∛ ( 3 3 ) ) × 1 6 = 3 × 1 6 =48
now , 4 8 2 =2304